Song folklore of the Crimean Tatars: the aspect of identification (part 1) - Rustem Komurdzhi (Крымское историческое обозрение)
oday, a certain circle of Crimean Tatars and not only offer the society the idea of renaming the people to “Kyrym” using the expressions “Kyrymly”, “Kyrym khalky” arising from this name. Such a challenge was followed by the reaction of the academic part of scientists involved in transliteration, translation of ancient documents, manuscripts, according to which the evolution of the indigenous people of Crimea, its language, culture and statehood is recreated. Their counter-concept is the preservation of the lexeme “kyrymtatar”.